(untitled) (Indian Journal of Child Health, 2018)
Background: Nephrotic syndrome (NS) is a common chronic renal disorder in children. Oral glucocorticoids are required in high doses for prolonged periods adding to various comorbidities including psychosocial issues and behavioral problems. Objectives: This study was done to analyze the behavioral profile of children with steroid-sensitive NS (SSNS), also its association with other factors such as mothers’ education, socioeconomic status, and age distribution. Materials and Methods: This was a questionnaire (child behavior checklist)-based cross-sectional study conducted at a tertiary care center. Children from 6 to 15 years with diagnosis of SSNS for the duration of 1 year or more were included in the study. Cases were divided into two groups: Infrequent and frequent relapsing NS (IFRNS)/steroid-dependent NS (SDNS). Equal number of children in 6–15 years age group attending outpatient clinic was taken as controls. Results: Children with SSNS (n=161) had behavioral problems in significant percentage (39.13%) compared to the control group (8.75%). It was observed more in boys (73.02%) who had more hyperactive, aggressive behavior, and externalizing problems. Internalizing problems (anxious/depressed, withdrawn/depressed, and somatic complaints) were significantly more in the study group (17.39%) as compared to none in the control group. Children with FRNS/SDNS course had more significant problems compared to relapse IFRNS group. Age distribution, socioeconomic status, and mother’s education had no significant effect on its occurrence. Conclusion: Significant behavioral problems are observed in children with SSNS and are related to the type of SSNS.